Experimental of Micropitting Corrosion of Gear based on Profile Modification - Dongfei Wang; Shijun Liu; Lü Pangong; Jiqiang Li; Deming Meng (Jixie chuandong)
The addendum and root of involute gear are modified，and the modified gear and unmodified gear are placed on the contact fatigue tester for comparative test. The variation of micro pitting corrosion on the tooth surface is reflected by measuring the profile fluctuation deviation and the tooth surface morphology. The experimental results show that the size and area of micropitting corrosion of the modified gear are much smaller than those of the unmodified gear under the same number of cycles，the micropitting propagation rate of the modified gear is also much lower than that of the unmodified gear. When the gear fatigue failure occurs，the number of cycles of the profile modification gear is much higher than that of the unmodified gear. It can be concluded that the profile modification greatly improves the anti micropitting ability and contact fatigue property of the gear.